Glacio-geomorphic Study on Submarine Morphology East of Lutzow-Holm Bay, East Antarctica - OMOTO, Kunio (Faculty of Science, Tohoku University, 1976)
application/pdf 紀要類 (bulletin) 8975070 bytes departmental bulletin paper